The correlation of gold, exchange rate, and stock market on Covid-19 pandemic period - Alfi Syahri; Robiyanto Robiyanto (University of Merdeka Malang, 2020)
This study aims to analyze the correlation of gold, exchange rate, and CSPI on COVID-19 pandemic periods by testing the effect of gold exchange prices and exchange rate on CSPI and stock volatility. Also, by considering the dynamic correlation of dynamic correlations between CSPI with gold and CSPI with exchange rates. The data was collected from secondary data in the form of JCI daily data, gold prices, and exchange rate during the COVID-19 pandemic period from January 2020 to June 2020. Further, the data was analyzed by using a GARCH method to examine the effect of changes in gold and USD prices for CSPI and stock volatility. Hence, DCC-GARCH method was used to see the dynamic correlation between CSPI with gold and IHSG with exchange rate. The result showed that changes of gold prices has significant effect of on stock price volatility, the presence of a positive dynamic correlation between CSPI and gold, and a negative dynamic correlation between CSPI and exchange rates. This research can be used as a reference for investors for their investments by looking at the relationship between the CSPI, gold, and the exchange rate. JEL Classification: G10, G11, G12DOI: https://doi.org/10.26905/jkdp.v24i3.4621